Biological Aspects of Spiny Rock Crab, Thalamita crenata in Kolono Bay, South Konawe, Southeast Sulawesi: Segi Hayati Rajungan Hijau (Thalamita crenata) di Teluk Kolono, Konawe Selatan, Sulawesi Tengara - Hamid, Abdul; Kamri, Syamsul; Nurjannah, Atun (Habitus Aquatica, 2024)
The aim of this study was to determine the relationship carapace width and body weight, condition factor, sex ratio, stage of gonad maturity, first sizesexual maturity, and fecundity in the Kolono Bay. Crab samples were obtained using folding trap fishing gear. The resultas of this study were that distribution of carapace width and body weight of male and ovigerou female T. crenata tended to be greater than that of females. While thecarapace width and body weight of female T. crenata tended to be smaller than body size of thecorrelation between carapace width and body weight of T. crenatashows a very shows a strong andpositive relationship with negative allometric growth patterns. . Male condition factors were significantlydifferent (p <0.05) from ovigerous females and females. Male and female condition factors weresignificantly different (p <0.05) indicating that the male was greater than the female. Overall sex ratiowas significantly different (p <0.05) from the 1: 1 ratio, except in the period July and August. Gonadmaturity stages based on sex and ovigerous females were found to vary during research but weredominated by the mature of gonads. The carapace width of the first sexual maturity this crab, male and female, were 55.39mm and 49.53 mm, respectively with fecundity ranged from 32.741 to 257.798.